2019
DOI: 10.1186/s12884-019-2406-4
|View full text |Cite
|
Sign up to set email alerts
|

Change in prevalence of gestational diabetes and obstetric complications when applying IADPSG screening criteria in a Belgian French speaking University Hospital. A retrospective cohort study

Abstract: Background In April 2012 our institution chose to switch from a two- step criteria for Gestational Diabetes Mellitus (GDM) screening, to the International Association of Diabetes in Pregnancy Study Group (IADSPG) criteria. This shift led to an increased prevalence of GDM in our pregnant population. We designed a study in order to estimate the magnitude of the increase in GDM prevalence before and after the switch in screening strategy. As a secondary objective we wanted to evaluate if there was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…In the current study, we observed that the prevalence of GDM increased by more than a factor of 4 from 2005 to 2017, and by 3 comparing the two study periods. This rise of prevalence is in line with previous studies after the new criteria were adopted [11,31,32]. In Spain, GDM prevalence increased 3.3 times (10.6 to 35.5%), in the USA 2.8 times (5.5% to 15,6%) and 4.5 times in Japan (2.9% to 13%) using the IADPSG criteria [13,33,34].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the current study, we observed that the prevalence of GDM increased by more than a factor of 4 from 2005 to 2017, and by 3 comparing the two study periods. This rise of prevalence is in line with previous studies after the new criteria were adopted [11,31,32]. In Spain, GDM prevalence increased 3.3 times (10.6 to 35.5%), in the USA 2.8 times (5.5% to 15,6%) and 4.5 times in Japan (2.9% to 13%) using the IADPSG criteria [13,33,34].…”
Section: Discussionsupporting
confidence: 89%
“…However, it should be noted that GDM prevalence (35.5%) and risk factors occurrence in this Spanish population were particularly high compared to those reported in our and other studies study population [32,34,41,43]. Conclusively, countries with high GDM prevalence and risk factor burden might benefit most from adopting of the IADPSG screening criteria to substantially improve perinatal outcomes to an extent of being able to ignore the drawbacks of increased medical cost.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…This method was devised to determine whether linear regression would provide a suitable projection. However, we expected there could be large distortions in the data due to the change in our scoring method and the known increase in prevalence when using the IADPSG diagnostic criteria compared with older criteria [29][30][31][32]. Method 3 involved linear regression of only the previous IDF Diabetes Atlas HIP edition estimates that showed a consistent trend, followed by extrapolation from the age-adjusted 2019 HIP estimate.…”
Section: Methodsmentioning
confidence: 99%
“…There are no RCTs that have compared treatment of GDM based on the IADPSG criteria with no treatment. Some observational studies reported no difference or even an increase in adverse perinatal outcomes, 46,47,[50][51][52][53][54][55] whereas others showed a significant improvement in perinatal outcomes associated with the use of the IADPSG criteria [56][57][58] (Table 3).…”
Section: Screening For Gdm Between 24 and 28 Weeks Of Pregnancymentioning
confidence: 99%